PENGGUNAAN MODEL MIND MAPPING DALAM PENINGKATAN PEMBELAJARAN PKN SISWA KELAS IV SEKOLAH DASAR - fatimah, feti (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract: The Using of Model Mind Mapping in Improving PKn Learning in Elementary School Four Grade Students. The purpose of this research is to describe the step of using mind mapping model in enhancement PKn learning fourth grade students in  elementary school. This research uses class actions research methods are carried in the three cycles. Each cycle consists of planing, action, observation, and reflection. The data source of this research is the fourth grade students of Petarangan elementary school Kemranjen Banyumas in academic year 2012/2013 which amounted to 22 students, consist 11 men adn 11 women. Data collecting methods are collected through observation, interview, test, and documentation. The validity of data using the triangulation technic and resource. The data Analysis is used by this research in kuantitatif and kualitatif data analysis. Research procedure is Suharsimi Arikunto model. The result showed that the using of  Model Mind Mapping in Improving PKn Learning in  Elementary School. Keywords: Mind mapping model, PKn learning. Abstrak:Penggunaan Model Mind Mapping dalam Pembelajaran PKn Siswa Kelas IV Sekolah Dasar. Penelitian ini bertujuan untuk mendeskripsikan langkah-langkah penggunaan  model Mind Mappingdalam peningkatan pembelajaran PKn siswa kelas IV Sekolah Dasar. Penelitian ini menggunakan metode  penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Setiap  siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SD Negeri Petarangan  Tahun Ajaran 2012/2013 yang berjumlah 22 siswa, terdiri dari 11 siswa laki-laki dan 11 siswa perempuan. Teknik pengumpulan data adalah dengan observasi, wawancara, tes dan dokumentasi.  Validitas data menggunakan triangulasi teknik dan sumber. Analisis data menggunakan teknik analisis kualitatif dan kuantitatif. Prosedur penelitian adalah model Suharsimi Arikunto. Hasilnya menunjukkan bahwa penggunaan model Mind Mapping dapat meningkatkan pembelajaran PKn di Sekolah Dasar. Kata Kunci:Model Mind Mapping, Pembelajaran PKn